2018
DOI: 10.1080/07380577.2018.1491084
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating Fieldwork Settings: Matching Student Characteristics to Demands

Abstract: Academic fieldwork coordinators (AFWCs) face the challenge of matching students to Level II fieldwork (FW) sites. This study surveyed 301 fieldwork educators (FWEs) from 30 states to explore how important it was for students to possess 25 characteristics or abilities to enable success at the educators' individual work sites. The top three characteristics and abilities overall were as follows: (1) time management, (2) ability to communicate with supervisor when help is needed, and (3) overall professional behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…The students in our study reported having clinical preceptors who modeled flexibility and adaptability facilitated their ability to demonstrate the same characteristics. Clinical preceptors highly value these characteristics in students as well and have reported these were among the important characteristics for students to possess for successful clinical education experiences 27 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The students in our study reported having clinical preceptors who modeled flexibility and adaptability facilitated their ability to demonstrate the same characteristics. Clinical preceptors highly value these characteristics in students as well and have reported these were among the important characteristics for students to possess for successful clinical education experiences 27 …”
Section: Discussionmentioning
confidence: 99%
“…Clinical preceptors highly value these characteristics in students as well and have reported these were among the important characteristics for students to possess for successful clinical education experiences. 27 Second, students reported their readiness was fostered by clinical preceptors who exhibited excellent verbal communication skills. For example, students reported that routinely communicating with the clinical preceptor before a patient session helped them develop a framework with which to predict and plan for multiple elements of the patient encounter including communication strategies, prioritised examination, patient education and intervention needs and individualised discharge considerations.…”
Section: Implication For Preceptorsmentioning
confidence: 99%
“…For example, Kemp and Crabtree (2018) investigated the match between student characteristics and demands of practice education settings. The top six characteristics and abilities practice educators rated that occupational therapy students needed to demonstrate to be successful on placements were time management, communication with supervisor when help was needed, overall professional behavior, ability to make change based upon supervisor's feedback, flexibility with schedule changes, and organizational skills (Kemp and Crabtree 2018). Hills et al (2016) delved into Generation Y students' views and preferences about the provision of feedback during practice education.…”
Section: Clinical and Practice Education: Evidence From The Student P...mentioning
confidence: 99%
“…Sin embargo, hay autores que sugieren que la asignación de los estudiantes a los dispositivos debería contemplar el repertorio de habilidades de las que disponen y que puede adecuarse mejor a unos contextos laborales que a otros. En este sentido apoyan que el valor de que los coordinadores de prácticas combinen las habilidades personales y profesionales de los estudiantes con las demandas de configuración antes de las asignaciones a los recursos (Kemp & Crabtree, 2018), algo que según Gangaway & Stancanelli (2007) ayudaría a disminuir la ansiedad y el estrés que se puede experimentar durante las experiencias de prácticas.…”
Section: Introductionunclassified